Phylogenetic relationships of the orchid genus coelogyne in peninsular Malaysia inferred from morphological characteristics and Internal Transcribed Spacer (ITS) - Yoh, Kok-Hon; Yong, Christina Seok-Yien; Ong Abdullah, Janna; Go, Rusea (Penerbit Universiti Kebangsaan Malaysia, 2022)
The phylogenetic relationships among the Peninsular Malaysian orchid genus Coelogyne were studied by morphological characteristics and sequence data of the internal transcribed region (ITS) from the nuclear ribosomal DNA (nrDNA). Coelogyne is a large genus of about 200 species distributed in pantropical areas from the Himalayas, Sri Lanka, India, Southern China and throughout South East Asia to Papua New Guinea. The widely accepted previous classification system was exclusively based on floral morphology. There were very few molecular systematic studies of Coelogyne done in Peninsular Malaysia thus far. In this study, 59 Coelogyne samples were collected throughout Peninsular Malaysia and 57 of them were identified to the species level. To study the phylogeny of this genus, morphological characters were utilized together with molecular evidences to generate the systematic hypotheses. Cluster analysis was performed using both the vegetative and floral characters. The results showed that three sections of Peninsular Malaysian Coelogyne, namely Longifoliae, Speciosae, and Fuliginosae were sister groups which were more closely related by forming one clade by itself. Another clade consisted of four other sections, namely Flaccidae, Coelogynae, Tomentosae, and Verrucosae. Molecular phylogenies obtained by using the Neighbour-Joining method showed the close relationship between the sections Tomentosae and Verrucosae, whereas usage of the Maximum Likelihood method demonstrated that three sections, namely Longifoliae, Speciosae, and Fuliginosae, were sister groups since they formed a single clade.